The analysis of carcass value in pigs of different genotypes - M. Čechová; V. Mikule (Czech Journal of Animal Science, 2004)
In an experiment the analysis of some traits of carcass value in pigs of Czech Large White and Landrace breeds differentiated according to the genotype of C-MYC and MYF4 genes was carried out. PCR-RFLP method was used for gene determination. In CLW pigs three genotypes of C-MYC gene were found out with a frequency of allele A 0.714 and B 0.286, in L pigs the BB genotype was not detected. In CLW pigs the respective frequencies of allele A and B of MYF4 gene were 0.660 and 0.340, in L breed 0.917 and 0.083. There was a statistically significant difference in the levels of MLLT area (P ≤ 0.05) between the genotypes AA, AB and BB of C-MYC gene in CLW pigs. In this breed statistically significant differences (P ≤ 0.05) were detected between the genotypes AA and AB in these traits: MLLT area, percentage of main lean cuts and weight of main lean cuts in favour of genotype BB of MYF4 gene. We did not find any significant differences in the measured levels of carcass value traits between different genotypes of MYF4 gene in L breed.